2016
DOI: 10.4142/jvs.2016.17.4.583
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofSalmonella entericaand Shiga toxin-producingEscherichia coliin zoo animals from Chile

Abstract: Salmonella (S.) enterica and Shiga toxin-producing Escherichia coli (STEC) are foodborne pathogens. Here, we report the prevalence of S. enterica and STEC in feces of 316 zoo animals belonging to 61 species from Chile. S. enterica and STEC strains were detected in 7.5% and 4.4% of animals, respectively. All Salmonella isolates corresponded to the serotype Enteritidis. To the best of our knowledge, this is the first report of S. Enteritidis in the culpeo fox (Lycalopex culpaeus), black-capped capuchin (Sapajus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Coincident with our study, other studies carried out in Chile have found these common serovars to be Enteritidis, Typhimurium and Infantis (serogroup D, B and C1) [ 15 , 18 , 22 , 24 , 27 , 28 , 29 , 30 ]. However, S. Enteritidis has represented the highest percentage of isolates [ 15 , 16 , 17 , 18 , 19 , 22 ]. In Chile, the Institute of Public Health has reported that S. Enteritidis is the most common serovar associated with human illnesses [ 27 , 28 ], accounting for 61% of all Salmonella cases [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coincident with our study, other studies carried out in Chile have found these common serovars to be Enteritidis, Typhimurium and Infantis (serogroup D, B and C1) [ 15 , 18 , 22 , 24 , 27 , 28 , 29 , 30 ]. However, S. Enteritidis has represented the highest percentage of isolates [ 15 , 16 , 17 , 18 , 19 , 22 ]. In Chile, the Institute of Public Health has reported that S. Enteritidis is the most common serovar associated with human illnesses [ 27 , 28 ], accounting for 61% of all Salmonella cases [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Chile, the presence of Salmonella strains has been reported in different sources including water used for irrigation [ 14 ], backyard flocks [ 15 ], wild animals [ 16 , 17 , 18 , 19 ] and chicken eggs [ 18 ]. One study depicted a prevalence of MDR Salmonella of 13% in 35 strains obtained from irrigation water [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…(20)(21)(22)(23)(24). Although infection of humans with salmonella serovars in zoos is not common, there is some published data demonstrating the outbreaks of non-typhoid Salmonellosis in zoo visitors.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies investigating the prevalence of STEC strains as a public health risk have screened and isolated STEC strains from different sources, including synanthropic animals. STEC isolates were identified ( stx1 and/or stx2 positive but eae negative) in the order Artiodactyla in zoo animals from Chile, isolating STEC for the first time from Thomson’s gazelle ( Eudorcas thomsonii ) [25]. Other studies have detected STEC strains in stool samples from asymptomatic children and domestic animals (cattle, a guinea pig, and a chicken) from households in a semirural community in Ecuador; however, STEC symptomatic disease in humans seems to be rare in this country [26].…”
Section: Discovery Of Stec Serotypes and Novel Virulence Factors Imentioning
confidence: 99%